Cooperation: AS Survival Calculus: State Interest and Power Asymmetry in the ASEAN-UN Joint Strategic Plan of Action on Disaster Management (2021-2025). - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Andi Zarkarsyih Nur; Nafisa Wanda Vertika Sari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2026)
Abstract This study examines why states invest in multilateral cooperation in disaster management despite the availability of unilateral alternatives, using a defensive structural realist approach to the ASEAN–UN Joint Strategic Plan of Action on Disaster Management (JSPADM) 2021–2025. The objective of this research is to analyze whether state interests, power asymmetry, and sovereignty considerations can explain the prioritization, resource commitments, and implementation dynamics within the plan. The study employs process tracing and structured content analysis of official documents, high-level communiqués, and operational records. The findings reveal five main patterns: (1) the framing of national interest as a means of enhancing security, (2) resource contributions shaped by state power, (3) the securitization discourse of disasters, (4) institutional design that preserves sovereignty, and (5) relative gains dynamics reflected in ASEAN centrality and leadership competition. These findings indicate that ASEAN member states engage in the JSPADM insofar as participation enhances national resilience and regional standing while maintaining acceptable sovereignty costs. The study contributes by demonstrating that defensive structural realism remains relevant for analyzing non-traditional security issues, particularly in explaining disaster cooperation as a product of strategic calculation rather than mere normative convergence.